Analysis of Groundstrap Installation on Fuel Consumption Efficiency and Exhaust Gas Emissions on Motorcycles - Mudrikah, Mudrikah; Permadi, Luchyto Chandra; Arifin, Muhammad; Primadiarta, Ari Sam; Bambang Widjanarko, Bambang Widjanarko; Djarot Winoto, Djarot Winoto; Zubdatu Zahrati, Zubdatu Zahrati; Kusyairi, Imam (Universitas Kristen Cipta Wacana, 2024)
Efforts to improve performance on the system ignition motorbike already Lots done, one of them Can done with installation Groundstrap on cable spark plug For as cable grounding spark plugs for voltage fire from coil will focus going to spark plugs. Research This use method study descriptive For know difference use Groundstrap ( Groundstrap Aluminum and Copper ) against characteristics voltage cable spark plug. Testing done as much as three trials, 4000 Rpm, 6000 Rpm, and 8000 Rpm. Data analysis techniques using descriptive statistics For knowing the average and percentage the changes. Based on results analysis of research data that has been discussed in the section previously, can withdrawn conclusion with use Groundstrap Copper capable reducing CO exhaust gas by -3.58% reduction. while Groundstrap Aluminum experience increase in CO exhaust gas by 4.48 %. Likewise with HC exhaust gas, Groundstrap Copper capable reducing HC exhaust gas by -4.63 %. While Groundstrap Aluminum experience increase in HC exhaust gas by 6.66%. So it can be concluded the more the good thing is system ignition on a vehicle so will the more low exhaust emissions released. On consumption material burn Groundstrap Copper capable lower consumption material fuel consumption on motorbikes decreased by -6.1%. Meanwhile, Groundstrap Aluminum consumption material burn become increase by 1.53%.